Ocena częstości występowania bólu głowy oraz objawów mu towarzyszących = Assessment of the frequency of the occurrence of headaches and associated with them symptoms - Katarzyna Kożuch; Piotr Kozłowski; Magdalena Kozłowska; Izabela Ławnicka (Journal of Education, Health and Sport, 2016)
Kożuch Katarzyna, Kozłowski Piotr, Kozłowska Magdalena, Ławnicka Izabela. Ocena częstości występowania bólu głowy oraz objawów mu towarzyszących = Assessment of the frequency of the occurrence of headaches and associated with them symptoms. Journal of Education, Health and Sport. 2016;6(5):11-20. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50903